The Future as a Cultural Commons: Grammars of Commonality in Crisis‐Ridden Wilhelmsburg - Louis Volont (Social Inclusion)
In this article, I analyze how vulnerable yet resistant urban residents set out to “common” a particular phenomenon: the future. The scene in analysis is Wilhelmsburg, the southern section of the German city of Hamburg. Plagued by industrial pollution, infrastructural decay, and systemic poverty, Wilhelmsburg’s residents united themselves around the 2000s in an organization called Future Wilhelmsburg. Their goal? To get out of the crisis by commoning Wilhelmsburg’s future. Future Wilhelmsburg has engaged ever since in a continuous struggle—writing, blogging, researching, advocating, and protesting—to subject the neighborhood’s future to the wishes of its residents rather than to the top‐down projections of the urban governmental elite. The future of Wilhelmsburg is thus approached as a “cultural commons”: a symbolic construct that is collectively produced yet intrinsically vulnerable to enclosure. Against this background, I set out to sociologically explain Future Wilhelmsburg’s commoning of the future. How is it, precisely, that the activists united in Future Wilhelmsburg manage to turn the “not yet” into a meaningful matter of common concern? Laurent Thévenot’s “pragmatic sociology,” and more precisely his model of the three “grammars of commonality”—referring to the structuring principles through which social actors turn individual concerns into collective ones—allows us to answer this question. The article highlights how the “justificatory grammar" (structuring activists’ public argumentations), the “liberal grammar” (structuring their pinpointing of collective paths forward), and the “affective grammar” (structuring their affinity to place) all permeate the work of Future Wilhelmsburg as it sets out to turn the future into a cultural commons.